Cloud vs. Local Development Stacks: Leveraging CDE and PaaS Platforms for Academic Web Development Labs - Raffi Ihza Zuhairnawan; Umar Yunan K. S. Hediyanto; Muhammad Fathinuddin (eProceedings of Engineering, 2026)
In the era of the Fourth Industrial Revolution, technical skills in web application development are increasingly crucial for information technology students. This paper presents a comparative study of cloud-based and local development stacks within the context of a Web Application Development practical course at a local academic institution. The study benchmarked four CDEs (GitHub Codespaces, CodeSandbox, Jetify Devspace, and DevZero) and four PaaS platforms (Koyeb, Render, Northflank, and Lade) across parameters including performance, network latency, booting time, and features. A final comparison contrasts these cloud systems with a traditional local setup. The findings indicate that GitHub Codespaces and Koyeb represent the most suitable combination of CDE and PaaS for this practical course due to their technical capabilities, ease of use, and instructional practicality. Furthermore, the cloud-based target system, utilizing GitHub Codespaces and Koyeb, proved superior to the existing local development system across most parameters, offering a more inclusive, efficient, and scalable solution. Future research may incorporate wider platforms and integrations. Keywords—Web Application Development, Cloud Development Environment, Platform-as-a-Service, GitHub Codespaces, Koyeb